Development of rubberized geopolymer interlocking bricks - Mohammed, B.S. (Elsevier Ltd, 2018)
Waste tires contribute badly to the environment on a huge scale as they are bulky, non-biodegradable, and prone to fire and being a shelter for mosquitos and other insects. This paper reports on a novel approach towards the development of rubberized brick by utilizing crumb rubber as the sole fine aggregate in the production of geopolymer interlocking bricks. The response surface methodology (RSM) from Design Experts software has been used to determine the numbers of trial mixes and their corresponding ingredients. A total of thirteen trial mixes were carried out and tested for compressive strength and the RSM model was developed to predict the design mix based on the targeted compressive strength. The mix design was obtained to be an 18 M for NaOH and 0.8 solution to fly ash ratio. The geopolymer interlocking rubberized bricks were then produced and tested for compressive strength, dimension, modulus of rupture, water absorption, initial rate of absorption, and efflorescence. The geopolymer interlocking rubberised bricks presented a low compressive and flexural strength and a high-water absorption capacity. The bricks were rated as non-effloresced and classified as 3rd class bricks which can be used as non-load bearing material. It is recommended to utilize nano silica in order to increase the strength of the brick. Â© 2018